Semantic Verbal Fluency Pattern, Dementia Rating Scores and Adaptive Behavior Correlate With Plasma Aβ42 Concentrations in Down Syndrome Young Adults - Hoyo, Laura Del; Xicota, Laura; Sánchez-Benavides, Gonzalo; Cuenca-Royo, Aida; Sola, Susana de; Langohr, Klaus; Fagundo, Ana B.; Farré, Magí; Dierssen, Mara; Torre, Rafael de la (Frontiers in Behavioral Neuroscience, 2015)
Down syndrome is an intellectual disability disorder in which language and, specifically, verbal fluency are strongly impaired domains; nearly all adults show neuropathology of Alzheimer’s disease, including amyloid deposition by their fifth decade of life. In the general population, verbal fluency deficits are considered a strong Alzheimer’s disease predictor being the Semantic Verbal Fluency Task (SVFT) a useful tool for enhancing early diagnostic. However, there is a lack of information about the association between the semantic verbal fluency pattern (SVFP) and the biological amyloidosis markers in Down syndrome. In the current study, we used the SVFT in young adults with Down syndrome to characterize their SVFP, assessing total generated words, clustering, and switching. We then explored its association with early indicators of dementia, adaptive behavior and amyloidosis biomarkers, using the Dementia Questionnaire for Persons with Intellectual Disability (DMR), the Adaptive Behavior Assessment System-Second Edition (ABAS-II), and plasma levels of Aβ peptides (Aβ40 and Aβ42), as a potent biomarker of Alzheimer's disease. In Down syndrome, worse performance in SVFT and poorer communication skills were associated with higher plasma Aβ42 concentrations, a higher DMR score and impaired communication skills (ABAS–II). The total word production and switching ability in SVFT were good indicators of plasma Aβ42 concentration. In conclusion, we propose the SVFT as a good screening test for early detection of dementia and amyloidosis in young adults with Down syndrome.